Analysis of the Application of Operational Management in Manufacturing Companies in Bandung City: The Effect of Production Efficiency, Product Innovation, and Customer Satisfaction on Financial Performance - Suseno, Bambang Dwi; Sugianto, Efendi; Purnamasari, Eva; Supriadi, Asep (Westscience Press, 2023)
The operational management of manufacturing companies in Bandung City plays a pivotal role in shaping their financial performance. This quantitative research aimed to analyze the implementation of operational management, with a focus on production efficiency, product innovation, and customer satisfaction, and their effects on financial performance. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to assess these relationships. The research involved a sample of 130 manufacturing companies, spanning various sizes. The study found robust support for the following hypotheses: production efficiency positively influences financial performance, product innovation has a positive impact on financial performance, higher customer satisfaction is associated with improved financial performance, and there are significant interdependencies among production efficiency, product innovation, and customer satisfaction, collectively affecting financial performance. The findings emphasize the need for a holistic approach to operational management, innovation, and customer-centric strategies in manufacturing companies. These results provide valuable insights for managers and policymakers in Bandung City, offering practical recommendations for enhancing financial performance in the manufacturing sector.